Fine-needle aspiration cytopathology correlation study of thyroid nodule with the postoperative histopathological reporting in a rural medical setup - Rufus K Sam Vargis; Tony Joe Peechatt; C R Raghuveer; M S Sharada; Arun Mathew Chacko; Arya Vijayan (Wolters Kluwer Medknow Publications, 2022)
Background: Fine-needle aspiration cytology (FNAC) is the examination of cells that are obtained through a fine needle under vacuum. Due to the superior diagnostic reliability and cost-effectiveness of FNAC, American thyroid association had setup some guidelines stating that FNAC must be used as a diagnostic test initially before the ultrasonography and thyroid scintigraphy. This present study was undertaken to categorize and correlate all the thyroid FNAC samples according to the Bethesda system and for assessing the efficacy of the Bethesda reporting system in the preoperative evaluation of thyroid lesions. The major aim of study is to identify the nodules which require surgery and those benign nodules that can be observed clinically, thereby reducing the overall rate of thyroidectomy among patients with benign disorders. Materials and Methods: The present prospective study was conducted among 428 patients with thyroid lesions at a tertiary care rural medical set up. All the specimens were fixed in 10% formalin, and detailed gross examination was done. 3-10 tissue bits were selected from representative areas and all the bits were processed and stained with H and E stain. Cytological diagnoses were correlated with histopathology and the efficacy of The Bethesda System for Reporting Thyroid Cytopathology for reporting FNAC was estimated. Discussion: Out of 428 patients with thyroid lesions, 96 cases of histopathological specimens were collected. The histopathology lesions were divided into benign nonneoplastic, benign neoplastic, and malignant to study the gender, age group affected with these lesions and to calculate the association of malignancy with gender and age. The result showed that diagnostic tests are not significantly different with respect to sensitivity. Hence, FNAC is a reliable test for histopathology in diagnosis of thyroid lesions. In the present study, although the malignancy rate was higher among males, no association of gender and malignancy was not significant (P > 0.05). Conclusion: The Bethesda standardized system for reporting cytopathology improved the communication between pathologists and clinician promoting an interlaboratory agreement.